What successful students do: evidence-based learning activities matter for students' performance in higher education beyond prior knowledge, motivation, and prior achievement - Bosch, Eva; Seifried, Eva; Spinath, Birgit (Learning and individual differences, 2021)
In higher education, students must manage their learning on their own. When students seize the opportunity to engage in specific evidence-based learning activities, this should contribute to their achievement beyond their individual learning prerequisites (i.e., prior knowledge and motivation) and their prior achievement. In turn, students with higher motivation should use more learning activities. To test these hypotheses, two cohorts of students attending a lecture class on educational psychology participated in online-surveys at the beginning and the end of one semester (N1 = 112; N2 = 171). Using regression analyses, we found that learning activity use explained students' performance at the end of the semester beyond their learning prerequisites and prior achievement. Furthermore, students who valued educational psychology more used more learning activities. Overall, students used learning activities much less than intended at the beginning of the semester. In conclusion, the results point to the importance of students' learning behaviors and their potential to determine their own success. Further research should identify factors that help students put their intentions into practice.
Gesehen am 03.11.2021